2015
DOI: 10.1186/s12955-015-0265-x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in patient-reported physical health between cardiac and musculoskeletal diseases: systematic review and meta-analysis of population-based studies

Abstract: Population-based assessments of physical health are important to evaluate healthcare resource allocation. Normative data on the level of physical impairments attributable to specific diseases and severity levels within these diseases is critical to interpreting such data. Our objective, by means of a systematic review and meta-analysis, was to test the hypothesis that specific diseases which form cardiovascular and musculoskeletal disease spectra are associated with gradients of physical impairments. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…22 Individuals 43–70 years with IHD report worse physical HRQoL (38.9 (95% CI 36.9 to 41.0)) compared with the general population. 23 Similar results are reported in women with obstructive (41.9, SD 8.9) and non-obstructive heart disease (43.7, SD 9.4) (p=0.072). 24 Moreover, a decline in physical vs mental HRQoL is more predictive of hospital readmission 25 and mortality in healthy middle-aged and older women (n=40 337) 26 and in men and women with heart disease.…”
Section: Introductionsupporting
confidence: 80%
“…22 Individuals 43–70 years with IHD report worse physical HRQoL (38.9 (95% CI 36.9 to 41.0)) compared with the general population. 23 Similar results are reported in women with obstructive (41.9, SD 8.9) and non-obstructive heart disease (43.7, SD 9.4) (p=0.072). 24 Moreover, a decline in physical vs mental HRQoL is more predictive of hospital readmission 25 and mortality in healthy middle-aged and older women (n=40 337) 26 and in men and women with heart disease.…”
Section: Introductionsupporting
confidence: 80%
“…Constant pain greatly affects physical and mental functioning, contributing to decreased quality of life. A previous review of population-based quality-of-life studies found that the HRQoL of OA remained one of the worst compared with other chronic conditions [44,45]. The estimated SF-12 scores for OA from the studies included in our review were better than those summarized in previous reviews [45] but still remain relatively low and comparable to that of breast cancer patients [46].…”
Section: Discussionmentioning
confidence: 67%
“…The poor quality of life of these venous leg ulcer patients is shown by their mean SF-12 physical component score of 38.4. For comparison, a review of SF-12 and SF-36 scores in cardiovascular disease [ 22 ] reported the mean physical component to be 44.4 in hypertension patients, 38.9 in ischaemic heart disease, and 35.9 in heart failure, so these patients had similar physical quality of life to patients with ischaemic heart disease. For mental quality of life, our participants’ mean score was 49.6, very similar to 50 in the standard population.…”
Section: Discussionmentioning
confidence: 99%